Comparative analysis of dietary patterns and depression risk: significant inverse association with HEI-2015 and mediating role of BMI - Wang, Zicheng; Fang, Lei; Shi, Fachao; Cui, Qin; Zhou, Xiaomei (Frontiers in Nutrition, 2025)
ObjectiveDepression is a severe global mental disorder closely associated with dietary habits. This study aimed to evaluate associations between four dietary patterns [assessed by Dietary Inflammatory Index (DII), Healthy Eating Index-2015 (HEI-2015), Dietary Index for Gut Microbiota (DI-GM), and Composite Dietary Antioxidant Index (CDAI)] and depression risk. For any dietary pattern showing significant association, we further examined whether BMI mediated this relationship.MethodsData from the National Health and Nutrition Examination Survey (NHANES, 2007–2018) were analyzed. Four dietary indices were calculated using two 24-h dietary recalls: DII, HEI-2015, DI-GM, and CDAI. Depression severity was assessed via the Patient Health Questionnaire-9 (PHQ-9). Logistic regression and mediation analysis were employed to examine diet-depression associations and BMI’s mediating effect. For any dietary pattern showing significant association with depression, employ SHapley Additive exPlanations (SHAP) analysis to identify which specific dietary components contribute most to this association.ResultsHEI-2015 showed a significant negative correlation with depression (OR = 0.99, 95% CI: 0.98–1.00, p = 0.002). Compared to the lowest HEI-2015 quartile (Q1), the highest quartile (Q4) had significantly reduced depression risk (OR = 0.66, 95% CI: 0.50–0.87, p = 0.003). No significant associations were observed for DII, DI-GM, or CDAI. Mediation analysis revealed BMI partially mediated the HEI-2015–depression relationship (mediation proportion = 6.39%, p < 0.0001). SHAP analysis identified added sugars, whole fruits, and saturated fats as key HEI-2015 components: added sugars and whole fruits reduced depression risk, while saturated fats increased it.ConclusionThis study confirms a significant inverse association between HEI-2015 and depression risk, with BMI acting as a partial mediator. Reducing intake of added sugars and saturated fats while increasing whole fruits consumption may mitigate depression risk.